2012
DOI: 10.3109/00207454.2012.744309
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Patients Affected by Glioblastoma Treated With Radiotherapy: The Role of Serum Hemoglobin Level

Abstract: Our data suggested that extent of surgery and RPA class remain independent prognostic factor, whereas patients' anemia did not adversely affect prognosis in glioblastoma elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The finding that low hemoglobin level is significantly associated with a lower survival rate of GBM patients is consistent with the known fact that tendency toward anemia is linked to lower survival rates in cancer patients (23,25). In the context of GBM, several works supported low hemoglobin levels as a poor prognostic factor (16)(17)(18)(19)26), though other works were less supportive of this notion. Fiorentino and Fusco (26) studied the effect of hemoglobin level of mostly biopsied elderly GBM patients (median age of 71 years) and found that a hemoglobin level cutoff of ≥12 g/dL was not significantly related to overall survival but did show better progression-free survival.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The finding that low hemoglobin level is significantly associated with a lower survival rate of GBM patients is consistent with the known fact that tendency toward anemia is linked to lower survival rates in cancer patients (23,25). In the context of GBM, several works supported low hemoglobin levels as a poor prognostic factor (16)(17)(18)(19)26), though other works were less supportive of this notion. Fiorentino and Fusco (26) studied the effect of hemoglobin level of mostly biopsied elderly GBM patients (median age of 71 years) and found that a hemoglobin level cutoff of ≥12 g/dL was not significantly related to overall survival but did show better progression-free survival.…”
Section: Discussionsupporting
confidence: 77%
“…This work was supported by subsequent works showing similar results (17,18). Nevertheless, some works failed to demonstrate the significant prognostic value of hemoglobin level for GBM (18,19,26). Another parameter recently studied is RDW, which reflects a degree of variation (anisocytosis) in the size of the circulating red cells.…”
Section: Introductionsupporting
confidence: 56%
“…As shown in Table 2, pretreatment HGB, MCH, RBC, and HCT were not correlated with the OS of patients with GBM in our study. Similarly, a previous study showed that the HGB level did not influence clinical outcome in elderly patients with GBM [18]. However, Céfaro et al revealed that a low HGB level was associated with shorter OS in patients with high-grade gliomas [19].…”
Section: Discussionmentioning
confidence: 92%
“…More recently (2020), Kismar-Elbaz et al [6] found that low hemoglobin levels (<12 g/dL [females] or <14 g/dL [males]) was a negative prognostic factor for survival, leading the authors to conclude that measures should be taken to normalize preoperative hemoglobin levels and red cell distribution width to improve prognosis. Notwithstanding the findings of those studies, other studies have not found any association between hemoglobin levels and prognosis in these patients [18,19]. In our previous study [17], we hypothesized that low levels of hemoglobin would increase HIF expression.…”
Section: Discussionmentioning
confidence: 76%